The Influence of Ease of use of Information Technology, Information Quality and Top Management Support on SME Performance Through End User Satisfaction: A Study on Semarang City SMEs - Koerniawan, Iwan; Triatmanto, Boge; Zuhroh, Diana (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
This research aims to analyze the influence of ease of use of information technology, information quality and top management support on SME performance through end user satisfaction in SMEs in the city of Semarang. The contribution of this research is as feedback for SME managers or owners in making decisions regarding the importance of digitizing accounting, in this case the accounting information system. This research is quantitative research with an explanatory research approach that is guided by a questionnaire that tests the relationship and influence between research variables. Data analysis was obtained using the SEM approach by analyzing 132 respondents who had used the accounting information system application for at least 1 year. The results reveal that ease of use of information technology, quality of information and top management support have a significant effect on SME performance through end user satisfaction of accounting information.